Socio-Demographic Factors and Health-Oriented Behaviors of University Students in the Podkarpackie Region. Long-Term Prospective Research - Więch, Paweł; Bazaliński, Dariusz; Chmiel, Zdzisława; Ratajczyk, Józef; Januszewicz, Paweł; Binkowska-Bury, Monika (Regional Barometer. Analyses & Prognoses, 2018)
The aim of the study was to achieve a prospective long-term evaluation of the impact of socio-demographic factors on students, and their healthy behaviors. It was a diagnostic survey employing a standardized interview questionnaire. The survey was conducted among 905 first-year students of medical and non-medical faculties (18–19 years of age), and the University of Rzeszów, and Rzeszów University of Technology. It was conducted in 2009 and repeated two years later. The rating of the behavior patterns of students was conducted in accordance with the following schedule: October 2009 – January 2010 (T1), October 2011 – January 2012 (T2). The level of healthy behaviors in 2012 increased significantly in a positive direction compared to 2009 (p